Pengaruh Fasilitas Wisata terhadap Kepuasan Konsumen di Pantai Pohon Cinta Kecamatan Marisa Kabupaten Pohuwato - Titi hawanda Metania Cono; Bulan Suci Ramadhani; Sofyan Laginda (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the attractions in The Love Tree Beach Tour affects tourist satisfaction, to find out whether the facilities in The Love Tree Beach Tourism affect tourist satisfaction and to find out whether the tariffs charged at Pohon Cinta Beach can affect tourist satisfaction, This study uses explanatory types with quantitative descriptions. Sampling in this study used probability sampling techniques by simple random sampling. The data collection method is to use a questionnaire that is distributed to as many as 100 tourists who have visited The Love Tree Beach. Based on the analysis of data from the study shows that 61% feel satisfied, 25% feel very satisfied and 14% feel dissatisfied with Love Tree Beach Tourism, in terms of available facilities, it seems that 65% of samples are satisfied, 20% are dissatisfied and 12% feel very satisfied, in terms of the tariffs charged, it can be seen that 68% of samples are satisfied, 17% are very satisfied and 10% feel dissatisfied. Based on the results of the research, it can be seen that most respondents chose to be satisfied with the facilities contained in the Love Tree Beach Tourism Location, Marisa District, Pohuwato Regency as many as 61% were satisfied from 100 respondents and only 1% chose not to be satisfied with the facilities provided.